Desain dan Uji Coba Media Pembelajaran E-learning Berbasis Blog Pada Materi Sistem Periodik Unsur - Zona Octarya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2022)
The average of students and teachers at Islamic Senior High School of Nurul Hidayah Sungai Salak already have Android. However, students tended to use Android just as the communication, entertainment, and social media tools.   Even though, it could be used to support them in the learning process, namely applicative learning media. The solution for students’ Android can be utilized optimally by designing an E-Learning learning media in the form of a Blog on priodic system of elements lesson. This research aimed at knowing the levels of validity, practicality, and student response to Blog based E-Learning learning media on Periodic System of the Elements lesson that was developed. It was a Research and Development (R&D) with Borg and Gall development model that 10 steps were reduced to 5. The subjects of this research were a material expertlecturer, a media expert lecturer, a Chemistry subject teacher, and 10 the tenth-grade students atIslamic Senior High School of Nurul Hidayah Sungai Salak. The research findings showed that the levels of validity and practicality of Blog based E-Learning learning media were stated very valid and very practical with the assessment percentages bya material expert, a media expert, and a Chemistry subject teacher continuously 100%, 96%, and 100%. The result of student response overall to Blog based E-Learning learning mediadeveloped was very good. Therefore, it was very peasible to be used as a learning media at school, so that, it would had a positive impact and optimalize the use of Android by student.